A new species of Matelea s. l. (Apocynaceae, Asclepiadoideae) from México - Lozada‒Pérez, Lucio; Alvarado-Cárdenas, Leonardo O. (Phytotaxa, 2016)
It is herein described Matelea cervantesii as a new species for the Mexican flora. The new species is endemic to southern Mexico and it is morphologically akin to Matelea crenata (Matelea subgenus Heliostemma). Comparative illustrations are also provided in the present work.